Histomorphological study of postnatal changes in the bulbourethral gland of buffalo - ANURAG, ANURAG; SAIGAL, R P; SETHI, R S (The Indian Journal of Animal Sciences, 2014)
The postnatal changes in the bulbouretheral gland in buffaloes (17) aged 6 months, 1-1.5 vears, 2-2.5 years and > 3.5 years with 5. 4, 4 and 4 animals in each group, respectively, were studied. The histological investigations revealed that the bulbourethral gland in bufthlo was compound tubulo-acinm type. At 6 months of age the lobulation was not distinct and the parenchyma comprised of ducts, tubular invaginations and non-Iuminated solid cell masses. The lobulation became distinct at prepubertal age. Mucous acini appeared at pubetty. Characteristic glands with predominant mucous acini developed in adults. Epithelium of intralobular ducts varicd from cuboidal to columnar type while main secretory ducts had transitional type epithelium even at 6 months of age.